2017
DOI: 10.17219/acem/68270
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related risk factors for perioperative stroke after carotid endarterectomy in symptomatic patients

Abstract: Background. Carotid endarterectomy (CEA) is a surgical procedure used in ischemic brain stroke prevention in patients with symptomatic and asymptomatic severe carotid artery stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…35 Stelagowski et al showed that men and women have separate risk factors for perioperative stroke following CEA with hypercholesterolemia being a more influential risk factor in men than in women. 36 While we were unable to demonstrate any significant factors which would explain the higher rates of eCD in women, outcome differences based on sex remain an unresolved issues in carotid revascularization studies.…”
Section: Discussionmentioning
confidence: 64%
“…35 Stelagowski et al showed that men and women have separate risk factors for perioperative stroke following CEA with hypercholesterolemia being a more influential risk factor in men than in women. 36 While we were unable to demonstrate any significant factors which would explain the higher rates of eCD in women, outcome differences based on sex remain an unresolved issues in carotid revascularization studies.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies reported that women undergo endarterectomies less often than men. However, in some, but not all, studies women have higher rates of post-endarterectomy TIA, strokes, and mortality (Akbari et al, 2000;James et al, 2001;Sarac et al, 2002;Stela ˛gowski et al 2017).…”
Section: Phasementioning
confidence: 99%